Integrating Ecological Lifestyle Education into Teaching Citizen Education at Secondary School in Vietnam - A Content Perspective (Journal of Contemporary Educational Policies and Practices, 2021)
Ecological lifestyle and ecological lifestyle education for students has recently been a concerned issue as unsustainable development leads to countless negative effects on the environment. Based on document analysis and theoretical framework, the author aims at generalizing several theories of ecological lifestyle, ecological lifestyle education and proposing certain contents of ecological lifestyle that can be integrated into teaching the Citizen Education subject at Junior Secondary School in Viet Nam for both the current curriculum and the new curriculum applied from 2018. The practical significance of this research paper is to propose teaching contents for integrating ecological lifestyle together with lists of textbook sessions suitable for integrating these contents in the current curriculum and the 2018 curriculum. These are valuable suggestions for teachers during organizing teaching activities.
Keywords: ecological lifestyle; ecological lifestyle education; Citizen Education; integration